The difficulty of steering settlement development to reduce the loss of ecosystem services: an exploration of different development scenarios in Switzerland using spatially explicit land-use models - Schwaab, Jonas; Lautenbach, Sven; Braun-Dubler, Nils; Gmünder, Markus; Grêt-Regamey, Adrienne; Strien, Maarten Jan van (Journal of environmental planning and management, 2020)
To reduce the negative environmental impact of settlement development, a range of policy instruments are available. Empirical studies have highlighted advantages and disadvantages of different instruments, including tradable development rights (TDRs) and zoning. We add to this knowledge by developing a land-use modelling framework that can be used to assess the potential impact of different policy scenarios on the spatial pattern of settlement development and the potential loss of ecosystem services. We compare the impact of four scenarios that are inspired by different policy instruments. Our results show that limiting the urban growth in certain municipalities or regions has a high impact on ecosystem services. Thus, the definition of sending and receiving areas as employed in TDR programs could be very useful. However, possible trade-offs will have to be taken into consideration, in particular between the protection of fertile agricultural soils and the protection of valuable nature areas.
Online veröffentlicht: 17. July 2019
Gesehen am 19.02.2026